2000
DOI: 10.1054/bjoc.2000.1429
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen use and intentional exposure to ultraviolet A and B radiation: a double blind randomized trial using personal dosimeters

Abstract: A previous randomized trial found that sunscreen use could extend intentional sun exposure, thereby possibly increasing the risk of cutaneous melanoma. In a similarly designed trial, we examined the effect of the use of sunscreens having different sun protection factor (SPF) on actual exposure to ultraviolet B (UVB) and ultraviolet A (UVA) radiation. In June 1998, 58 European participants 18–24 years old were randomized to receive a SPF 10 or 30 sunscreens and were asked to complete daily records of their sun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(72 citation statements)
references
References 24 publications
4
65
1
2
Order By: Relevance
“…In contrast to NCTC 2544 and empty vector control cells (NCTC-EV), the basal mRNA expression of AHR in NCTC-shAHR KC was decreased by approximately 80% (Figure 1a). Irradiation with 200 J/m 2 UVB, equivalent to the minimal erythema dose of fair-skinned individuals, 17 led to a significantly lower induction of the AHR target genes CYP1A1, COX-2, and plasminogen activator inhibitor-2 (PAI-2; involved in regulation of extracellular matrix degradation 18 ) in NCTC-shAHR cells compared with NCTC 2544 and NCTC-EV cells (Figure 1b), providing evidence that AHR signaling is significantly suppressed in these KC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to NCTC 2544 and empty vector control cells (NCTC-EV), the basal mRNA expression of AHR in NCTC-shAHR KC was decreased by approximately 80% (Figure 1a). Irradiation with 200 J/m 2 UVB, equivalent to the minimal erythema dose of fair-skinned individuals, 17 led to a significantly lower induction of the AHR target genes CYP1A1, COX-2, and plasminogen activator inhibitor-2 (PAI-2; involved in regulation of extracellular matrix degradation 18 ) in NCTC-shAHR cells compared with NCTC 2544 and NCTC-EV cells (Figure 1b), providing evidence that AHR signaling is significantly suppressed in these KC.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous findings that UVB exposure of KC increases the expression of CYP1A1 and COX-2 in an AHR-dependent manner, it was postulated that AHR signaling contributes to the development of UVB-induced NMSC, 4,14 an idea that is further strengthened by the results of our present study. As the UVB doses used in this study, with 200 J/m 2 being equivalent to the minimal erythema dose of fair-skinned human individuals, 17 can be easily reached during recreational sunbathing, we propose that a transient antagonism of this signaling pathway, especially in times of extensive UV exposure, will be beneficial for the prevention of NMSC. It will be interesting to see, if this newly described anti-apoptotic…”
Section: Discussionmentioning
confidence: 98%
“…This same concern has been advanced in studies showing that population that used sunscreen had greater melanocytic nevi, an indicator of sun exposure [9,10,11,12,18,19,148], although a recent study from Canada found that sunscreen reduced nevi in a randomized prospective design [74]. The negative effects of sunscreen may be most evident when individuals choose to be outdoors in the sun rather than when their time in the sun is determined by factors out of their control such as work schedules.…”
Section: Does Sun Safety Increase Time In the Sun?mentioning
confidence: 93%
“…16,17 These trials were representative of sun exposure behaviors of millions of light-skinned young subjects eager to acquire a tan during holidays or during leisure times. The 2 trials demonstrated that sun exposure, mainly sunbathing, was 19-25% longer duration with use of SPF 30 than with use of SPF 10 sunscreens.…”
Section: The European Randomized Trialsmentioning
confidence: 99%